2007
DOI: 10.1680/grim.2007.11.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tamper weight shape on dynamic compaction

Abstract: This paper presents the effect of tamper weight shape on the dynamic compaction method in granular soils. Although the dynamic compaction method appears to be very simple, it requires careful design of the compaction process. The aim of this study is to improve the efficiency and decrease the cost of deep compaction by using cylinder-shaped tamper weights. The influence of the shape of the bottom of the tamper weight on dynamic compaction efficiency was evaluated experimentally on sandy soils. Sands of three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…The results of field penetration test are shown in table (2) and according to these results most of the soil is either loose or medium in its relative density and with depth the soil becomes dense.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of field penetration test are shown in table (2) and according to these results most of the soil is either loose or medium in its relative density and with depth the soil becomes dense.…”
Section: Resultsmentioning
confidence: 99%
“…The most popular formula which is used in this study to predict the depth of improvement is Menard formula [2].…”
Section: Dynamic Compactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have used numerical methods to evaluate the mechanism of dynamic compaction (Pan and Selby 2002; Arslan et al 2007;Kopf et al 2010;Li et al 2010;Jia and Zhou 2010;Ghassemi et al 2010;Jahangiri et al 2010). Also experimental and physical modeling has been used to study this phenomenon (Jafarzadeh 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the efficiency of dynamic compaction with the conical-based pounder depended on both the grain size characteristics and the volume change behaviour of the sand. Arslan et al (2007) investigated the effect of tamper weight shape and the influence of the shape of the bottom of the tamper weight on the dynamic compaction method in granular soils experimentally. They studied conical-bottom tamper weights with the conic angles having approximately the same values as the internal friction angles of the three different densities of soil.…”
Section: Introductionmentioning
confidence: 99%